Readiness of prospective elementary school teachers for project-based hybrid learning in social studies course - Dewi, Sari; Yani, Muhammad Turhan; Surjanti, Jun; Prasetya, Sukma Perdana (Edelweiss Applied Science and Technology, 2025)
The effectiveness of PjBHL is measured in terms of dimensions such as motivation, prospective behavior, self-regulated learning, and ICT literacy both online and offline. The research aims to assess the preparedness of elementary teacher education students before engaging in social studies using the PjBHL model. Conducted in June 2025, this quantitative study involved 117 students (56 males and 61 females) from the Primary School Teacher Education Program at Universitas PGRI Kanjuruhan Malang. A Likert-scale questionnaire (1-4) was employed to evaluate student readiness in motivation, prospective behavior, self-regulation, and ICT proficiency. Descriptive statistics were used to analyze readiness levels, and MANOVA was applied to compare gender differences. The findings indicate that 1) students’ readiness for PjBHL was relatively good, rated as B+, and 2) motivation, prospective behavior, self-regulated learning, and ICT skills did not show significant differences based on gender. The study recommends that lecturers adopt adaptive, student-centered pedagogies that facilitate gender-neutral approaches, ensuring equitable learning opportunities for all students.